Emotional Social Development of 4 years old Children in Pandemic Time (COVID-19) - Dewi Ratih Rapisa; Hayatun Thaibah (Proceedings Series on Social Sciences & Humanities, 2021)
Not every child can successfully pass tasks in social-emotional development at an early age, so that various obstacles can occur. Educators and parents should understand children’s development by providing guidance, especially during a pandemic, which requires children to study at home. The research objective was to determine the social-emotional development of children aged four years during the pandemic (Covid 19). This research method is quantitative. The place of research was conducted in PAUD Terpadu Tarbiyatul Athfal, East Banjarmasin. The research subjects were 15 children aged four years—data collection techniques using closed questionnaires and observation. The results showed that the aspects of interaction with peers were equal to 100%. Friendly learning aspect and intense interaction aspect equivalent to 93.3%. Friendly part and starting to be more adaptable, equivalent to 33.3%. Elements of showing an attitude of cooperation, participation, group activities, and playing dramas are equal to 40%. This indicates that during the pandemic (Covid 19), interaction with peers was classified as very good even though there were still children whose development period was unknown.